2009
DOI: 10.1080/02699050902997870
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in children with acquired brain injury: Parent perspectives 1–5 years after injury

Abstract: Parents frequently reported poor quality of life and cognitive, emotional and behavioural problems in their children following TBI. These preliminary findings indicate that children, after TBI, are at risk of developing persistent clinical problems and require follow-up beyond the acute period of their recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
81
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 17 publications
11
81
1
Order By: Relevance
“…Postconcussion emotional dysfunction, including frustration, is not uncommon, especially in adolescent patients. In their study of parental ratings of child quality of life after a TBI, Limond et al 22 described persistent emotional and behavioral difficulties for the affected child. The feelings of frustration noted in our study appeared to stem from varied sources, including the nature and longevity of the physical symptoms, interpersonal relationships, and time missed from school and sport.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Postconcussion emotional dysfunction, including frustration, is not uncommon, especially in adolescent patients. In their study of parental ratings of child quality of life after a TBI, Limond et al 22 described persistent emotional and behavioral difficulties for the affected child. The feelings of frustration noted in our study appeared to stem from varied sources, including the nature and longevity of the physical symptoms, interpersonal relationships, and time missed from school and sport.…”
Section: Discussionmentioning
confidence: 99%
“…Limond et al 22 indicated that poorer post-TBI outcomes were linked to the absence of systematic, long-term follow-up and care. 22 Each interview lasted approximately 9.05 6 2.04 minutes and was centered on the participant's perceptions of the effect of the sport-related concussion on the adolescent's physical and emotional function, academic performance, and social interactions, which are the primary elements of adolescent HRQOL. Responses were obtained via a semistructured interview guide based on 5 open-ended questions (Appendix).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, 45% of parents reported that their child did not receive all the services needed during the mean of 4 years after their TBI. 35 An important limitation of the study is that we did not collect detailed data on therapy that patients received after discharge from the inpatient setting. In addition, there is a lack of national standards on the rehabilitation interventions children with TBI should receive, and wide variations both within and across institutions in the nature of care delivered.…”
Section: Discussionmentioning
confidence: 99%